Cell death in the gut epithelium and implications for chronic inflammation - Patankar, Jay V.; Becker, Christoph (Nature Reviews Gastroenterology & Hepatology, 2020)
The intestinal epithelium has one of the highest rates of cellular turnover in a process that is tightly regulated. As the transit-amplifying progenitors of the intestinal epithelium generate 300 cells per crypt every day, regulated cell death and sloughing at the apical surface keeps the overall cell number in check. An aberrant increase in the rate of intestinal epithelial cell (IEC) death underlies instances of extensive epithelial erosion, which is characteristic of several intestinal diseases such as inflammatory bowel disease and infectious colitis. Emerging evidence points to a crucial role of necroptosis, autophagy and pyroptosis as important modes of programmed cell death in the intestine in addition to apoptosis. The mode of cell death affects tissue restitution responses and ultimately the long-term risks of intestinal fibrosis and colorectal cancer. A vicious cycle of intestinal barrier breach, misregulated cell death and subsequent inflammation is at the heart of chronic inflammatory and infectious gastrointestinal diseases. This Review discusses the underlying molecular and cellular underpinnings that control programmed cell death in IECs, which emerge during intestinal diseases. Translational aspects of cell death modulation for the development of novel therapeutic alternatives for inflammatory bowel diseases and colorectal cancer are also discussed.
CRIS-Team Scopus Importer:2020-07-24